Utility of Blockchains in Publishing Sector: Focus on Academic Publishing - Poh Phung, Siew; Raju, Valliappan (International Journal of Psychosocial Rehabilitation, 2020)
Blockchain considers decentralized, automatic information, eventually making a mutual framework where exchanges are spared and put away. Logical data in its quintessence is a huge, unique assortment of data and information that is cooperatively made, modified, utilized and shared. It loans itself well to the blockchain innovation since that innovation can possibly tackle difficulties around companion survey, irreproducibility, and measurements. Different uses of blockchain innovation, for example, cryptographic forms of money and computerized rights the board frameworks additionally have a potential importance for scholarly distributing